Chemical synthesis of proteins containing post‐translational modifications and PNA‐templated disulfide bond formation - Li, Fupeng (2012)
The study of protein structure and function is a central topic of bioscience research. As the most important molecules of life, proteins often undergo post-translational modifications (PTM) in order to carry out their biological functions. A good example is the histone proteins whose PTMs include acetylation, methylation and ubiquitination on specific amino acid side chains. The understanding of how a protein exerts its function in either its native or post-translationally modified form can not only solve many problems in basic biology but also produce therapeutic breakthroughs in medicine. Protein chemical synthesis is a useful approach for the production of these modified proteins which are invaluable reagents for the structural and functional characterization of individual PTM events.